Intervention Effect of Long-Term Aerobic Training on Anxiety, Depression, and Sleep Quality of Middle School Students With Depression After COVID-19 - Luo, Lin; Song, Naiqing; Yang, Hao; Huang, JiaHong; Zhou, Ling; Zhang, Liping (Frontiers in Psychiatry, 2021)
Objective: To explore the effects of using RPE exercise intensity monitoring methods and 12-week mid- and low-intensity aerobic training on anxiety, depression and sleep quality of depressed middle school students after the COVID-19 epidemic.Methods: The subjects were all from a boarding middle school in Chongqing, China. All the subjects were screened by the self-rating depression scale and reached the diagnostic criteria for depression. The study subjects were divided into a control group（n=35）and an exercise group（n=34）. The exercise group performed 30-minute night aerobic running four times a week (using the exercise intensity of the RPE = 11-14), and the control group studied and lived normally. The experiment lasted 12 weeks in total. After the experiment, there were 34 people in the control group and 23 people in the exercise group. The subjects’ anxiety, depression and Pittsburgh sleep quality were scored before and after the experiment. Results: After intervention, the depression index(< 0.01) of the exercise group was significantly lower than that of the control group. Conclusion: Using the RPE exercise intensity monitoring method for 12 weeks of low-intensity aerobic training can improve the depressive symptoms of depressed middle school students, and it is beneficial to improve the students' mental health.